Performance of a Photovoltaic Pumping System - Serrano-Casares, Francisco Víctor; Cano-González, Miguel Ángel (My University, 2014)
Pumping water with solar photovoltaic (PV) is an application of particular interest in isolated systems. This technology has proven over the years to be an effective way to supply drinking water to communities, as well as for agricultural use (irrigation) and livestock (troughs). The earlier installations of PV pumping were based on the use of DC motors of medium and low power directly coupled to the PV generator operating centrifugal pumps. Later they have been proposing and using various types of systems based on different combinations of DC motors, AC motors, DC brushless motors, centrifugal pumps, positive displacement pumps, DC/DC converters and DC/AC inverters. They all have the common characteristic of being a result of specific developments to efficiently use in PV pumping systems. In this work a PV pumping system was installed on a building at the University of Malaga. The system simulates a conventional PV pumping system. A set of experiments has been carried out to study the performance of the system. In the installation studied, it has been proved that it is possible to improve the overall efficiency of the system by reducing the photovoltaic power installed to obtain the same volume of water. As a conclusion it may be said that a lower investment and less surface occupied by photovoltaic system is achieved.
In this work, a PV pumping system was installed in a building at the University of Malaga. The system simulates a conventional PV pumping system which in real conditions would supply a small agricultural installation. In the installation under examination it has been find that it is possible to improve the overall efficiency of the system obtaining a similar volume of water with a less photovoltaic modules installed. It can be concluded that the optimal performance allow a lower investment cost. Also a lower surface for the PV generator is a benefit.
Keywords: Energía fotovoltaica; Photovoltaic; Pumping system